2020
DOI: 10.1002/brb3.1721
|View full text |Cite
|
Sign up to set email alerts
|

A study on EEG feature extraction and classification in autistic children based on singular spectrum analysis method

Abstract: Autism spectrum disorder (ASD) is a serious neurodevelopmental disorder with core symptoms which include communication and social disorders and stereotyped behavior (Chez et al., 2006). The current incidence of ASD is rising rapidly around the world. The cause of ASD is presently unclear, and its diagnosis is mainly based on rating scales and behavioral observation, which are subjective. Therefore, it is worthwhile to find objective indicators for accurate assessment. Electroencephalography (EEG) is a powerful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 43 publications
0
29
2
Order By: Relevance
“…This is inconsistent with some of the studies using machine learning on resting-state EEG in ASD which reported classification accuracies above 87% 15 , 16 , 24 31 . However, the evaluation of the model performances were problematic in some of the studies.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…This is inconsistent with some of the studies using machine learning on resting-state EEG in ASD which reported classification accuracies above 87% 15 , 16 , 24 31 . However, the evaluation of the model performances were problematic in some of the studies.…”
Section: Discussioncontrasting
confidence: 86%
“…However, increased alpha power 13 and gamma power have also been reported in ASD 14 . Other spectral features, e.g., peak alpha frequency 15 , theta/beta ratio 16 and asymmetry 17 have also been associated with ASD. Besides spectral features, abnormal functional connectivity 18 , microstates 19 , and measurements of criticality 20 , 21 have also been found in ASD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the magnetic resonance imaging, electroencephalography (EEG) has its tremendous advantages for exploring the network deficits occurring in ASD patients, as well as providing a reliable biomarker for characterizing ASD [3], [28]. EEG provides a convenient and easy-operating way, which is well tolerated by children with ASD particularly, for measuring and understanding both resting brain activity and task-engaged states in ASD patients.…”
Section: Introductionmentioning
confidence: 99%
“…e increasingly high-end technological achievements make electronic information technology to be one of the most dynamic science and technology in the 21st century, which permeates all aspects of social development and cannot be replaced. Speci cally, its application features are as follows [4].…”
Section: Introductionmentioning
confidence: 99%